An Attempt to Recover a Paleomonsoon Signal in the Chinese Loess Plateau Using Anisotropy of Magnetic Susceptibility - Xian, Feng; Zhang, Rui (Frontiers in Earth Science, 2020)
The paleowind direction in the Chinese Loess Plateau (CLP) was studied using anisotropy of magnetic susceptibility (AMS) data. Magnetic fabrics were examined for the last glacial loess (L1) and last inter-glacial paleosol (S1) in the southern and central CLP along a present day precipitation zone of 600 mm per year. Statistical analyses of the orientations of AMS ellipsoids indicate that strong rainwater events may cause random distributions for the AMS azimuth of maximum axis and no deviation from the vertical plane for the average minimum axis. As high rainfall can distort paleowind analyses, it is challenging to conduct paleowind studies on the southern CLP - a topography of high precipitation density. Future studies could focus on the western and northern CLP, where there is less rainfall, making it more suitable for paleowind analysis by AMS.